Mastering adobe captivate 7 : create interactive SCORM-compliant demonstrations, simulations, and quizzes with Captivate 7 /: create interactive SCORM-compliant demonstrations, simulations, and quizzes with Captivate 7. (2012) - Unknown
No abstract available